Unlocking Purchase Intentions: The Impact of Social Media Marketing and E-WOM on Scarlett Products - Praatmana, Nanang Dwi; H., Ag. Sunarno; Sutono (Universitas Negeri Semarang, 2024)
The Indonesian cosmetics market is becoming increasingly competitive, with local brands such as Scarlett, gaining significant traction through social media. Previous studies report mixed findings regarding the influence of social media marketing and E-WOM on consumer purchase intentions. This study aims to measure the purchase intention of Scarlett products through social media marketing and E-WOM, using brand trust and consumer engagement as intervening variables. This study employs a quantitative approach. The population consists of skincare consumers in Indonesia, selected using purposive sampling with the criteria of being active social media users. A total of 180 respondents were selected. The collected data were analyzed using Structural Equation Modeling (SEM) AMOS. The results indicate that social media marketing and E-WOM do not directly affect purchase intention. However, they positively and significantly influence brand trust and consumer engagement. Moreover, brand trust and consumer engagement positively and significantly impact purchase intention. Finally, brand trust and consumer engagement fully mediate the relationship between social media marketing, E-WOM, and purchase intention for Scarlett products.